Analisis Vegetasi Hutan Kerangas Di Arboterum Nyaru Menteng Kalimantan Tengah - Sari Aulia Azizah; Kissinger Kissinger; Yusanto Nugroho; Hamdani Fauzi (Jurnal Serambi Engineering, 2020)
Environmental management in the Nyaru Menteng Arboretum Conservation area especially for the Kerangas forest has not been done much. This research was conducted to determine the analysis of vegetation in the Kerangas forest in the Arboretum conservation area. This research is expected to get the value of vegetation and important value index in the Kerangas forest, based on the results of the study there are 23 types of vegetation found at seedling level, 24 types of vegetation found at sapling level, 14 types of vegetation found on poles, 13 types of vegetation found at tree. Blumeodendron tokbrai vegetation has the highest value with a NIP value of 18,047 at the seedling level. Vegetation type Litsea sp. Has the highest value with a NIP value of 18,159 at the stake level. The vegetation type Syzygium lineatum, has the highest value with a NIP value of 44,584 at the pole level. Vegetation type Cratoxylon glaucum, has the highest value with a NIP value of 48,656 at the tree level.